2014
DOI: 10.1115/1.4027329
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Analysis of the Deformation of the Femoropopliteal Artery With Stenting

Abstract: Physiological loads that act on the femoropopliteal artery, in combination with stenting, can lead to uncharacteristic deformations of the stented vessel. The overall goal of this study was to investigate the effect of stent length and stent location on the deformation characteristics of the superficial femoral artery (SFA) using an anatomically accurate, three-dimensional finite element model of the leg. For a range of different stent lengths and locations, the deformation characteristics (length change, curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…No stent appears to accommodate all deformation modes without either exacerbating or restricting baseline deformations. Restriction of foreshortening within the stented segment observed in this study agrees with previous findings in patient 4,19 , cadaver 20 , and computational models 21 , and the amount of restriction for different devices correlates with device stiffness in compression determined with bench-top tests 8 . In these tests the Viabahn stent-graft restricted foreshortening the least, likely due to its helically wrapped wire around specially designed PTFE fabric, while most other devices contained multiple, rigid longitudinal connectors that restricted foreshortening.…”
Section: Discussionsupporting
confidence: 91%
“…No stent appears to accommodate all deformation modes without either exacerbating or restricting baseline deformations. Restriction of foreshortening within the stented segment observed in this study agrees with previous findings in patient 4,19 , cadaver 20 , and computational models 21 , and the amount of restriction for different devices correlates with device stiffness in compression determined with bench-top tests 8 . In these tests the Viabahn stent-graft restricted foreshortening the least, likely due to its helically wrapped wire around specially designed PTFE fabric, while most other devices contained multiple, rigid longitudinal connectors that restricted foreshortening.…”
Section: Discussionsupporting
confidence: 91%
“…While vessel shortening and increased curvature during knee flexion in both unstented and stented vessels have been widely reported, 1,2,5-7,10-17 this study for the first time found that more flexible stents accommodate shortening better than axially stiffer stents under axial compression during hip/knee flexion. Figure 6B demonstrates that stiffer stents, which shorten less, are associated with higher levels of curvature in the bare vessel immediately distal to the implanted stent.…”
Section: Discussionmentioning
confidence: 49%
“…Such kinking and buckling of the vessel at the ends of the stented segment has been associated with high stress concentrations within the vessel tissue, which may contribute to injury. 7 Clinical experience with FP stents has shown a positive correlation between stent flexibility and resistance to fracture. 8…”
Section: Introductionmentioning
confidence: 99%
“…Significant increase in the stress and strain on the stent, whether BES or SES, has been observed in the femoropopliteal system and the coronary artery system and affects long-term patency. [12][13][14] In addition, in vitro models assessing the influence of target vessel morphology demonstrate considerable alteration in stent function related to the underlying stent design in the curved vessel. 15,16 Stent placement in curved segments also can induce profound alterations in local hemodynamics affecting secondary flow patterns, pressure gradient change, and vorticity.…”
Section: Discussionmentioning
confidence: 99%